Totally laparoscopic resection using delta-shaped anastomosis of jejunal leiomyosarcoma with intussusception at the angle of Treitz: a case report - Kenichi Nakamura; Susumu Shibasaki; Seiji Yamada; Kazumitsu Suzuki; Akiko Serizawa; Shingo Akimoto; Masaya Nakauchi; Tsuyoshi Tanaka; Kazuki Inaba; Ichiro Uyama; Koichi Suda (Surgical Case Reports)
Abstract Background A leiomyosarcoma of the gastrointestinal tract is extremely rare. We report a case of jejunal leiomyosarcoma with intestinal intussusception at the angle of Treitz that was successfully treated with laparoscopic resection followed by intracorporeal reconstruction using a delta-shaped anastomosis. Case presentation A 54-year-old man was referred to our hospital due to fatigue and loss of appetite. Blood tests showed anemia. Enteroscopy and subsequent enterography using meglumine sodium amidotrizoate showed easily hemorrhagic tumor (10 cm in diameter) in the jejunum just beyond the angle of Treitz. Contrast-enhanced computed tomography revealed jejunojejunal intussusception. Histopathological examination of a biopsy specimen revealed a leiomyosarcoma. Laparoscopic resection of the tumor without reduction of the intussusception was performed. The resected line of the proximal intestine was very close to the ligament of Treitz in the present case. Intracorporeal jejunojejunostomy was completed using a delta-shaped anastomosis, wherein anastomosis was performed between the posterior walls of the proximal and distal jejunums after minimal mobilization around the ligament of Treitz. The patient’s postoperative course was uneventful, and he was discharged at 10 days postoperatively. No recurrence has been observed within 2 years after surgery. Conclusions We present a case in which a totally laparoscopic surgery for leiomyosarcoma located at the angle of Treitz with jejunojejunal intussusception was performed successfully.